Myocardial Perfusion Imaging Versus Computed Tomography Angiography–Derived Fractional Flow Reserve Testing in Stable Patients With Intermediate‐Range Coronary Lesions: Influence on Downstream Diagnostic Workflows and Invasive Angiography Findings. Issue 8 (22nd August 2017) - Nørgaard, Bjarne L.; Gormsen, Lars C.; Bøtker, Hans Erik; Parner, Erik; Nielsen, Lene H.; Mathiassen, Ole N.; Grove, Erik L.; Øvrehus, Kristian A.; Gaur, Sara; Leipsic, Jonathon; Pedersen, Kamilla; Terkelsen, Christian J.; et al.
Abstract : Background: Data on the clinical utility of coronary computed tomography angiography–derived fractional flow reserve (FFRCT ) are sparse. In patients with intermediate (40–70%) coronary stenosis determined by coronary computed tomography angiography, we investigated the association of replacing standard myocardial perfusion imaging with FFRCT testing with downstream utilization of invasive coronary angiography (ICA) and the diagnostic yield of ICA (rate of no obstructive disease, and rate of revascularization). Methods and Results: This was a single‐center observational study of symptomatic patients with suspected coronary artery disease referred to coronary computed tomography angiography between 2013 and 2015. Patients were divided into 3 historical groups based on the adjunctive functional testing approach: myocardial perfusion imaging (n=1332) or FFRCT "implementation" (n=800) or "clinical use" (n=1391). Propensity score matching was used to estimate the average period effect on outcomes. Patients in the FFRCT clinical use group versus the myocardial perfusion imaging group were older and had higher pretest probability of obstructive disease. After adjusting for baseline risk characteristics, there was a reduction in downstream ICA utilization (absolute risk difference: −4.2; 95% CI, −6.9 to −1.6; P =0.002). In patients referred to ICA, findings of no obstructive coronary artery disease decreased (−12.8%; 95% CI, −22.2 to −3.4; P =0.008) and rate of coronary revascularization increased (14.1%; 95% CI, 3.3–24.9; P =0.01), as did availability of functional information for guidance of revascularization (27.8%; 95% CI, 11.3–44.4; P <0.001) after clinical adoption of FFRCT . Conclusions: Replacing adjunctive myocardial perfusion imaging with FFRCT testing for functional assessment of intermediate stenosis determined by coronary computed tomography angiography in stable coronary artery disease was associated with less ICA utilization, and a higher ICA diagnostic yield. The findings in this observational study needs confirmation in prospective, randomized trials.